Cecília Meireles e a Índia: das provisórias arquiteturas ao êxtase longo de ilusão nenhuma - Oliveira, Gisele Pereira de [UNESP] (2014)
The presence of India in Cecília Meireles’s biography is considerable. The relationship between the poetess and India presents itself both explicitly and implicitly in her writings: on one hand, there is the title Poems written in India, parallel to it there are a lot of chronicles and lectures about this country; on the other hand, dozens of poems allow the inference of premises, nuances, and themes related to Indian philosophical and religious thought, related to Hinduism and/or Buddhism. In this present analysis, we started up based on the premise that it is unavoidable both considering the poems on India (Indian sceneries, daily life and individuals), and the inventory of philosophical/religious aspects in the poems, by means of interpretative analysis, showing that India and Indian thought appear in Cecília’s poetry vertically and horizontally. In this light, we dedicate the first analytical sections to the country as a place at which Cecília devotes her attention, employ as background for several poems, and from where she elects some individuals about whom she writes. We approach, firstly, the relationship between Cecília and India, by looking at biographical data, travel chronicles and the analysis of the poem Hymn for peaceful India. Then, we discuss the relationship between Cecília and two renowned Indian personalities, in whose honor she dedicated poems, lectures, etc., i.e., the Indian poet, thinker and educator Rabindranath Tagore, and the poem The most divine poet, and the pacifist Mohandas K. Gandhi, and the poem Mahatma Gandhi. After that, we focus on the book Poems written in India, result of her trip there in 1953, and we consider, on one hand, Cecília as a traveler, and, on the other, her view on Indian women and their work as we analyze two poems, Humility and Puri Women. The latter in comparison to another poem, Ballad for the ten...